Sequential biomolecular, macrofossil, and microfossil extraction from coprolites for reconstructing past behavior and environments - Blong, John C.; Whelton, Helen L.; van Asperen, Eline N.; Bull, Ian D.; Shillito, Lisa-Marie (Frontiers in Ecology and Evolution, 2023)
The study of macroscopic, microscopic, and biomolecular remains recovered from coprolites can provide a wide range of information on past human and animal behavior and environments. In earlier studies, research tended to focus on one or two proxies, but multiproxy approaches combining data from all remains within coprolites are becoming more common. Multiproxy analyses have demonstrated value for strengthening our understanding of the past and reducing equifinality. Here we present a sequential biomolecular, macrofossil, and microfossil extraction protocol that separates all different coprolite components and is intended as a best-practice guideline for coprolite analysis. We demonstrate the effectiveness of this method by applying it to an assemblage of coprolites from the Paisley Caves, Oregon, USA. By combining a wide range of proxies, this study provides important information on the taxonomy and behavior of organisms in the past as well as the paleoecological context of behavior.